Pengaruh Penggunaan Limbah Beton K-350 sebagai Pengganti Agregat Kasar terhadap Nilai Slump - Hartono, Chisa Kurniawan; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The development of construction technology in the era of globalization has progressed very rapidly, but on the other hand, it has also increased the amount of construction and demolition waste that has not been handled optimally. Waste from ready-mix concrete testing is one type of waste that has the potential to be reused as an alternative construction material. This study aims to determine the effect of using crushed stone from ready-mix concrete waste as a substitute for coarse aggregate on the workability properties of concrete as seen from the slump value. The concrete mix design method used in this study refers to the Department of Environment (DoE) method in SNI 03-2834-2000 with a planned concrete strength of 29 MPa. The test specimens were cylindrical concrete with 0% and 100% substitution of coarse aggregate using crushed concrete waste from the compressive strength test of K-350 concrete from PT Merak Jaya Beton. The slump test was carried out to assess the level of concrete mixture workability in each mix. The test results show that the slump value of concrete using coarse aggregate from concrete waste is still within the allowable range for structural works such as slabs, columns, and beams, which is 7.5–15 cm. The average slump value obtained was 13.86 cm, indicating that the concrete mixture still has good workability and can be easily applied in the field. Thus, the use of crushed concrete waste as a 100% substitute for coarse aggregate is still possible to be used in structural concrete mixtures in terms of workability.